Green Waqf-ILO C188 as an Islamic Social Finance Model for Decent Work in Fisheries - Imron Natsir; Eny Triastuti (LP2M IAIN Palopo, 2026)
Indonesia's fisheries sector plays a strategic role in food security, employment, coastal livelihoods, exports, and sustainable blue economy development. However, fisheries workers and fishing vessel crews remain exposed to informal employment relations, occupational safety risks, limited social protection, weak monitoring, and vulnerability to labor exploitation. The ratification of ILO Convention No. 188 through Presidential Regulation No. 25 of 2026 strengthens the normative basis for fisheries labor protection, yet its implementation requires sustainable compliance financing. This study aims to develop a Green Waqf-ILO C188 framework that integrates Islamic Social Finance with decent work and fisheries labor governance. This research uses a qualitative conceptual approach based on systematic literature review, policy analysis, and thematic synthesis of academic literature, institutional reports, regulations, and policy documents published mainly between 2020 and 2026. The findings show that zakat, waqf, green waqf, sadaqah, and blended Islamic social finance can support occupational safety, ethical recruitment, social protection, emergency assistance, and digital governance. The novelty lies in integrating Islamic Social Finance, ILO C188, decent work, SDG 8, SDG 14, ESG, and sustainable blue economy within one conceptual policy framework.